Solved! the 21 greatest PC mysteries. IN Features. - Broida, Rick.
Find out why your documents won't print, where your downloads disappear to, what a .dat file is, how those infernal toolbars invaded your browser, and much more.
Keywords: Digital Camera IMages (DCIM).; Thums.db.; File formats; BIOS